2003
DOI: 10.1073/pnas.1432450100
|View full text |Cite
|
Sign up to set email alerts
|

R5 HIV productively infects Langerhans cells, and infection levels are regulated by compoundCCR5polymorphisms

Abstract: Langerhans cells (LCs) are suspected to be initial targets for HIV after sexual exposure (by becoming infected or by capturing virus). Here, productive R5 HIV infection of LC ex vivo and LC-mediated transmission of virus to CD4 ؉ T cells were both found to depend on CCR5. By contrast, infection of monocyte-derived dendritic cells and transfer of infection from monocyte-derived dendritic cells to CD4 ؉ T cells were mediated by CCR5-dependent as well as DCspecific ICAM-3-grabbing nonintegrin-dependent pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
165
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(181 citation statements)
references
References 50 publications
14
165
2
Order By: Relevance
“…The mechanism of suppressed migration remains elusive, although it is unlikely to be due to the direct infection of DC. HIV and SIV can infect Langerhans cells (53,54); however, evidence for the significant infection of Langerhans cells during progressive infection is lacking. Moreover, Langerhans cells migrate with normal efficiency from the skin in SIV-infected monkeys at the time of peak virus load, indicating that failed Langerhans cell migration is not simply a function of high virus burden (23).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of suppressed migration remains elusive, although it is unlikely to be due to the direct infection of DC. HIV and SIV can infect Langerhans cells (53,54); however, evidence for the significant infection of Langerhans cells during progressive infection is lacking. Moreover, Langerhans cells migrate with normal efficiency from the skin in SIV-infected monkeys at the time of peak virus load, indicating that failed Langerhans cell migration is not simply a function of high virus burden (23).…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal simian immunodeficiency virus (SIV) infection of Rhesus macaques resulted in infected LC beneath the vaginal epithelium within the first day of infection [22]. Infection of biopsies of human cervical and skin of primate foreskin tissue explants show that LC can be infected [23,24]. Topical infection of human vaginal epithelial explants with HIV strongly suggested that LC and non-activated T-lymphocytes are the major cell types expressing HIV antigen in and emigrating from the explants and that they are often associated during emigration with HIV antigen concentrated at their contact region [21].…”
Section: Lc Interactions With Important Human Viruses Hiv and Lcmentioning
confidence: 99%
“…Post polymerase chain reaction (PCR) ligase detection reaction (LDR) analyses were used to genotype CCR5 promoter SNPs-2733, -2554, -2459, -2135, -2132, -2086, and -1835. Complete details of this genotyping strategy have been described in Kawamura et al [20].…”
Section: Dna Preparation and Genotyping Of Ccr5 Orf And Ccr5 Promotermentioning
confidence: 99%